2021
DOI: 10.1016/j.neuroimage.2021.118134
|View full text |Cite
|
Sign up to set email alerts
|

A 4-year longitudinal neuroimaging study of cognitive control using latent growth modeling: developmental changes and brain-behavior associations

Abstract: Despite theoretical models suggesting developmental changes in neural substrates of cognitive control in adolescence, empirical research has rarely examined intraindividual changes in cognitive control-related brain activation using multi-wave multivariate longitudinal data. We used longitudinal repeated measures of brain activation and behavioral performance during the multi-source interference task (MSIT) from 167 adolescents (53% male) who were assessed annually over four years from ages 13 to 17 years. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
0
13
1
Order By: Relevance
“…Regarding cognitive control as a moderating factor for the effect of hedonia, we found that higher hedonia was significantly associated with higher substance use, only for adolescents with higher activation in frontoparietal regions during cognitive control. Research suggests that higher frontoparietal activation during cognitive control reflects less efficient neural functioning ( Crone and Steinbeis, 2017 , Kim-Spoon et al, 2021 , Luna et al, 2010 ) and individuals with substance use dependence show inefficiency of frontoparietal cortical activity during delay discounting ( Monterosso et al, 2007 ). Importantly, our results demonstrate that hedonia can be a risk factor, particularly when it is coupled with inefficient cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding cognitive control as a moderating factor for the effect of hedonia, we found that higher hedonia was significantly associated with higher substance use, only for adolescents with higher activation in frontoparietal regions during cognitive control. Research suggests that higher frontoparietal activation during cognitive control reflects less efficient neural functioning ( Crone and Steinbeis, 2017 , Kim-Spoon et al, 2021 , Luna et al, 2010 ) and individuals with substance use dependence show inefficiency of frontoparietal cortical activity during delay discounting ( Monterosso et al, 2007 ). Importantly, our results demonstrate that hedonia can be a risk factor, particularly when it is coupled with inefficient cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Kim-Spoon and colleagues (2021) reported that as adolescents’ behavioral cognitive control improves with age, frontoparietal activation decreased and rACC activation increased, suggesting that lower frontoparietal activation and higher rACC activation may implicate better cognitive control. In addition, they demonstrated measurement invariance in longitudinal confirmatory factor analysis based on the multiple ROIs in the frontoparietal regions across four years, implying longitudinal reliability of ROI indicators during the MSIT task ( Kim-Spoon et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations